Learning Styles and its Relationship to Administrative Curiosity and Academic Achievement among of Management Students Department (Raparin Journal of Humanities (RJH), 2025)
The purpose of the study was to investigate the learning styles of management students Department and their relationship with academic achievement and administrative curiosity. To achieve this goal, the researcher designed two questionnaires. The first questionnaire focused on learning styles, based on Richard Felder and Barbara Solomon's framework, comprising (44) items. The second questionnaire measured administrative curiosity using a (35)-item scale similar to Campbell’s (1971) scale. They were applied after verifying its validity and reliability on a sample of (72) first-level students in the Administration Department at Kalar Technical College, Sulaimani Polytechnic University (SPU), during the academic year (2021-2022).The study revealed a higher preference for the practical-reflective learning style among the sampled students compared to the verbal-visual style. Both the holistic-sequential and sensory-intuitive styles ranked lower. Regarding gender differences, the practical-reflection style ranked first for male students, while sensory-intuitive style for male students and holistic-sequential style for female students ranked last. No significant gender-based differences were found in students' scores on the administrative curiosity scale.Furthermore, the results indicated a direct but non-significant relationship between students' scores on the learning styles scale and academic achievement, as well as a reciprocal non-significant relationship with administrative curiosity. Finally, the study found a direct, non-statistically significant relationship between students' scores on the administrative curiosity scale and academic achievement.The study concluded a list of recommendations.